PELATIHAN POST DISCHARGE PLANNING TERKINI - M. Lutfi; Rahmad Septian Reza (STIKES NGUDIA HUSADA MADURA, 2019)
The process of preparing a patient to return home is known as discharge planning. Discharge planning is a complex process and aims to prepare a patient for the transition in the hospital until the patient returns home. Based on Haris 2016's research, it was stated that 40% of patients were quite satisfied with discharge planning, 45.3% were satisfied, 14.7% said they were not satisfied. Based on the results of interviews conducted at the Syamrabu Hospital, Bangkalan Regency, it was revealed that health promotion and education as part of discharge planning was given only when the patient returned home, and was not clearly documented in a structured and integrated format. The method used in reforming agency activities related to discharge planning is a pilot study approach. This method starts from a situation analysis, making planning of action, implementation, evaluation, and gap analysis using a literature review. The data collection instruments used interviews, observation, document study and questionnaires. Interviews, observation and questionnaire distribution were carried out to the Head of the Nursing Division, the Head of the Nursing Section, the Head of the Room, the Chairperson. Furthermore, all teams are gathered together to be given direction or training related to the latest Discharge Planning Management. The participants of the activity were 20 nurses at the Syamrabu Hospital, Bangkalan Regency who attended the training activities. While participating in the activity, the nurse was very enthusiastic about the material presented. The nurse was also able to carry out the latest discharge planning. The training results were obtained before counseling was given to the knowledge of nurses in the sufficient category of 25% and the category of lacking 75%. After being given counseling, it increased into a good category, namely by 75%. Before being given training, the nurse's ability to be in the category of 0% and after being given the training, it increased to be in the good category, namely by 100%.